(untitled) (Research, Society and Development, 2020)
Objective: To investigate the influence of periodontal disease on serum levels of C-reactive protein (CRP), evaluating the levels of this biomolecule in patients with and without periodontal disease and, in those who have periodontal disease, evaluating the levels of this protein before and after periodontal treatment. Methodology: The research was carried out with 82 patients seen at the Clinic-School of Dentistry of the Federal University of Campina Grande, campus Patos-PB. The individuals were divided into two groups, one consisting of 42 patients with healthy periodontium and the other composed of 40 patients with periodontal disease. Among the individuals in the group with periodontal disease, 11 were reassessed one week after the completion of periodontal treatment. Results: CRP concentrations were significantly higher in the group with periodontal disease (6.09 ± 1.34 mg / l, n = 40) compared to the control group (2.93 ± 0.55 mg / l, n = 42). The results also showed that periodontal treatment reduced CRP values (3.76 ± 0.92 mg / l, n = 11) when compared to values before treatment (10.58 ± 3.69 mg / l, n = 11), however, with no statistically significant difference. Conclusion: It is observed that CRP levels are significantly increased in the serum of patients with periodontal disease compared to patients with healthy periodontium and that lower CRP levels were observed after non-surgical periodontal therapy. The results indicate that periodontal disease interferes with serum CRP levels, and that periodontal treatment can have a positive effect in reducing this protein.